Feeling close emotional intensity reduces perceived psychological distance. [article]. - Boven, Leaf Van
The results of 6 experiments indicate that emotional intensity reduces perceived psychological distance. People who described events emotionally rather than neutrally perceived those events as less psychologically distant, including embarrassing autobiographical events.(Experiment 1), past and future dentist visits. (Experiment 2), positive and negative events (Experiment 3), and a national tragedy (Experiment 6). People also perceived an event (dancing in front of an audience) as less psychologically distant when they were in a more emotionally arousing social role(of performer) than in a less emotionally arousing social role (of observer; Experiment 4). Two findings bolster the causal role of emotional intensity in reducing perceived psychological distance. First, reported emotional intensity was negatively correlated with perceived psychological distance and statistically mediated the effect of being in an emotionally arousing social role of perceived psychological distance (Experiment 4). Second, providing people with an alternative interpretation of their emotions (emotionally ambiguous whale songs) significantly reduced, even reversed, the negative correlation between self-reported emotional intensity and perceived psychological distance (Experiment5). These findings about emotional intensity are consistent with the broader idea that perceived psychological distance is grounded in an influenced by by the phenomenology of objective distance. Implications for theories of psychological distance, emotionality, and choice are discussed. -- (from the author)